Effect of Nano Vitamin E and Selenium Supplementation on Serum Biochemical Profile in Japanese Quails (Indian Journal of Animal Production and Management, 2024)
This study investigated the impact of nano vitamin E with Selenium on serum parameters in Japanese  quails. The experiment involved three groups: a control group (C1) fed a basal diet, a T1 group  receiving vitamin E (150mg/kg) and Selenium (0.3mg/kg), and a T2 group receiving nano vitamin E  (15mg/kg) and Selenium (0.03mg/kg). Results revealed significant differences (p
Keywords: Nano vitamin E; Selenium; Japanese quails; serum biochemistry